2013
DOI: 10.1007/s00520-013-2000-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of falls among community-dwelling older adults with cancer: results from the health and retirement study

Abstract: The consequences of falling can complicate the course of cancer treatment. Measures of functional limitations and balance have the potential to be quick and useful clinical tools to detect falling among seniors with cancer living in communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The articles are from 15 different countries, but especially from the United States of America (18)(19)(24)(25)30,33,39,(53)(54)(55)(56)(57)(58)(59)(60)(61) and Australia (17,28,32,34,36,42,44,(46)(47)52,(62)(63)(64) , with 16 and 13 studies, respectively. The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles are from 15 different countries, but especially from the United States of America (18)(19)(24)(25)30,33,39,(53)(54)(55)(56)(57)(58)(59)(60)(61) and Australia (17,28,32,34,36,42,44,(46)(47)52,(62)(63)(64) , with 16 and 13 studies, respectively. The other countries with most articles were Canada (23,29,40,(65)(66)(67)(68) with seven, Netherlands (20,31,35,51,69) with five, and United Kingdom (48,(70)(71)(72) with four.…”
Section: Resultsmentioning
confidence: 99%
“…This, and the guiding question, revealed that the risk factors for falls that are not listed in the NAN-DA-I are female (women are more prone to falls in the community) (20,38,40,59,63,(73)(74)77) , compromised activities of daily living (basic and instrumental) (16,22,25,31,33,(54)(55)63,70,73) , the fear of falling (30,(36)(37)(38)44,51,59,(62)(63)66,(70)(71)(72) , symptoms of depression/depression (18,30,43,45,51,59,63) , and lastly, low education (70) , low family income (70) , and ethnic minorities (70) . As for the level of evidence of these risk factors, we found that symptoms of depression/depression and female are mentioned in at least two papers , and compromised activities of daily living and fear of falling are mentioned in at least three random clinical trials (Ib evidence).…”
Section: Discussionmentioning
confidence: 99%
“…143 Community-dwelling older adult cancer survivors in the HRS who could not hold a full-tandem stance position for more than 30 seconds were 48% more likely to have fallen when reassessed 2 years later. 81 For the high-functioning senior, standing on foam or on 1 leg may provide a challenge sufficient to reveal more subtle deficits. Balancing on 1 leg, or "single limb stance," appears to be more challenging than tandem stance, 144 is associated with greater falls risk, 145 and, when tested bilaterally, may reveal lower limb asymmetries that can inform further examination and the selection of rehabilitative strategies.…”
Section: Balancementioning
confidence: 99%
“…Deficits on an ADL scale associate with falls risk in older prostate cancer survivors on ADT, 108 and those survivors in the HRS who had 1 additional functional limitation (items including walking, stairs, reaching) were 13% more likely to fall in the next 2 years than those who reported fewer limitation. 81 Identifying functional limitation and activity restrictions from the survivor's own perspective is an important part of goal setting in balance rehabilitation, particularly as patient-centered metrics gain recognition.…”
Section: Functional Limitations and Restricted Activitymentioning
confidence: 99%
“…). With regard to balance, cancer survivors are 50% more likely than similarly aged adults to self‐report difficulties with balance, and self‐reported balance issues are a strong indicator of future falls among cancer survivors (Chen & Janke ).…”
Section: Introductionmentioning
confidence: 99%